Steviol, an aglycone of steviol glycoside sweeteners, interacts with the pregnane X (PXR) and aryl hydrocarbon (AHR) receptors in detoxification regulation. (November 2017) - Dusek, Jan; Carazo, Alejandro; Trejtnar, Frantisek; Hyrsova, Lucie; Holas, Ondřej; Smutny, Tomas; Micuda, Stanislav; Pavek, Petr
Abstract: Stevia rebaudiana Bertoni is a herb known for the high content of natural sweeteners in its leaves. Its main secondary metabolite stevioside is used as non-caloric sweetener. No information, however, is available on whether stevioside or steviol interact with drug-metabolizing enzymes and pose the potential risk of food-drug interactions. Similarly, data are lacking on the interactions of steviol and stevioside with key nuclear receptors controlling the expression of the main drug metabolizing enzymes. We studied the interactions of steviol and stevioside with the pregnane X (PXR), vitamin D (VDR), constitutive androstane (CAR), farnesoid X (FXR), glucocorticoid (GR) and aryl hydrocarbon (AHR) receptors, which control expression of genes of xenobiotic metabolism. In addition, the inhibitory activities of steviol and stevioside towards the major cytochrome P450 enzymes CYP3A4, CYP2C9, CYP2D6, CYP1A2 and CYP2B6 were evaluated in vitro . We found that steviol moderately activated the PXR and AHR, resulting in the induction of their target genes including CYP3A4 and CYP1A2 in primary human hepatocytes. A weak inhibition of CYP3A4 and CYP2C9 with steviol was also found. Our results provide mechanistic data indicating that stevioside and stevia sweeteners may have the potential to induce food-drug interactions, a finding that warrants future prospective clinical investigation. Graphical abstract: Highlights: Stevioside and steviol are natural non-caloric sweeteners used in many countries. Not known if interact with cytochrome P450 drug-metabolizing enzymes. Steviol activates PXR and AHR, resulting in induction of CYP3A4 and CYP1A2 enzymes. Steviol is a weak inhibition of CYP3A4 and CYP2C9. Stevioside and stevia may have the potential to induce food-drug interactions.